A guide to writing research proposals the experimental method - Wan Chik Ibrahim (Penerbit Universiti Pendidikan Sultan Idris, 2007)
The simple language used in this book would allow ESL students better understand the basic of research. Though this book is only a guide to writing research proposals using the experimental method, it can be used as reference to writing research report after the actual research has been undertaken.